Recurrent Acute Chest Syndrome in Pediatric Sickle Cell Disease: Clinical Features and Risk Factors. Issue 1 (January 2018) - Patterson, Gaylen D.; Mashegu, Hafsat; Rutherford, Jordan; Seals, Samantha; Josey, David; Karlson, Cynthia; McNaull, Melissa; May, Warren; Carroll, Clinton; Barr, Frederick E.; Majumdar, Suvankar
Abstract : Acute chest syndrome (ACS) is a common and serious lung complication in sickle cell disease. A retrospective medical chart review was performed over a 6-year period in all pediatric ACS patients to investigate whether factors during the initial hospitalization were associated with recurrent ACS episodes. There were 386 episodes of ACS: 149 had only 1 episode of ACS, and 76 had >1 episode of ACS; 172 (76.4%) had hemoglobin SS, and 39 (17.3%) had hemoglobin SC. The most common presenting features were fever (83%), pain (70%), and cough (61%), which changed with the number of ACS episodes. Children <4 years old were at greatest risk of recurrent ACS ( P =0.018). In addition, history of asthma (adjusted incident rate ratio [IRR]=1.52; 95% confidence interval [CI], 1.22-1.98; P <0.0001), shortness of breath (IRR, 1.29; 95% CI, 1.02-1.62; P =0.033), and length of hospital stay (IRR, 1.04; 95% CI, 1.01-1.08; P =0.017) were significantly associated with prospective ACS events. Multiple episodes of ACS are common in sickle cell disease, and certain risk factors during the initial hospitalization are associated with recurrent ACS.